Star-shaped hole transport materials with indeno[1, 2-b] thiophene or fluorene on a triazine core for efficient perovskite solar cells. Issue 4 (11th January 2016) - Lim, Kimin; Kang, Moon-Sung; Myung, Yoon; Seo, Jong-Hyun; Banerjee, Parag; Marks, Tobin J.; Ko, Jaejung
Abstract : New star-shaped hole transport materials including a 1, 3, 5-triazine core have been successfully synthesized and investigated for high performance perovskite solar cells. Abstract : New star-shaped hole transport materials including a 1, 3, 5-triazine core have been successfully synthesized and investigated for high performance perovskite solar cells. A maximum power conversion efficiency of 13.2% has been achieved by employing 2, 2′, 2′′-(1, 3, 5-triazine-2, 4, 6-triyl)tris( N, N -bis(4-methoxyphenyl)-4, 4-dimethyl-4 H -indeno[1, 2- b ]thiophen-6-amine). The power conversion efficiencies of hole transport materials were comparable to that of the standardspiro-OMeTAD (13.8%).